Mitigation of AFB1-Related Toxic Damage to the Intestinal Epithelium in Broiler Chickens Consumed a Yeast Cell Wall Fraction - Hernández-Ramírez, Juan Omar; Merino-Guzmán, Rubén; Téllez-Isaías, Guillermo; Vázquez-Durán, Alma; Méndez-Albores, Abraham (Frontiers in Veterinary Science, 2021)
In vivo experiments were conducted to evaluate the effectiveness of a yeast cell wall fraction (YCW) to reduce the negative impact of aflatoxin B1 (AFB1) to the intestinal epithelium in broiler chickens. Zeta potential (ζ-potential), point of zero charge (pHpzc), Fourier transform infrared spectroscopy (FTIR), and scanning electron microscopy (SEM) techniques were used to characterize the YCW. Two hundred one-day-old male Ross 308 broiler chickens were randomly allocated into four treatments: (1) control, chickens fed an AFB1-free diet; (2) AF, chickens feed an AFB1-contaminated diet (500 ng AFB1/g); (3) YCW, chickens fed an AFB1-free diet + 0.05% YCW; and (4) AF + YCW, chickens fed an AFB1-contaminated diet (500 ng AFB1/g) + 0.05% YCW. At the end of the 21-day feeding period, fluorescein isothiocyanate dextran (FITC-d) was administered to chicks by oral gavage to evaluate gastrointestinal leakage. Blood and duodenum samples were collected to assess serum biochemistry and histomorphology, respectively. Compared to the control group, chicks of the AF group significantly diminished weight gain (WG) and average daily feed intake (ADFI), and increased feed conversion ratio (FCR), mortality rate (MR), and intestinal lesion scores (p < 0.05). Alterations in some serum biochemical parameters, and damage to the intestinal integrity were also evident in the AF-intoxicated birds. YCW supplementation improved WG and FCR and increased villus height, villus area, crypt depth, and the number of goblet cells in villi. The effects of YCW on growth performance were not significant in chicks of the AF + YCW group; however, the treatment decreased MR and significantly ameliorated some biochemical and histomorphological alterations. The beneficial effect of YCW was more evident in promoting gut health since chickens of the AF + YCW group presented a significant reduction in serum FITC-d concentration. This positive effect was mainly related to the changes in negative charges of YCW due to changes in pH, the net negative surface charge above the pHpzc, the higher quantities of negative charged functional groups on the YCW surface, and its ability to form large aggregates. From these results, it can be concluded that YCW at low supplementation level can partially protect broilers' intestinal health from chronic exposure to AFB1.